Clinical application of recommendations for neurobehavioral assessment in disorders of consciousness: an interdisciplinary approach - Murtaugh, Brooke; Shapiro Rosenbaum, Amy (Frontiers in Human Neuroscience, 2023)
Accurate diagnosis, prognosis, and subsequent rehabilitation care planning for persons with Disorders of Consciousness (DoC) has historically posed a challenge for neurological care professionals. Evidence suggests rates of misdiagnosis may be as high as 40% when informal beside evaluations are used to determine level of consciousness. The presence of myriad medical, neurological, functional (motor, sensory, cognitive) and environmental confounds germane to these conditions complicates behavioral assessment. Achieving diagnostic certainty is elusive but critical to inform care planning, clinical decision making, and prognostication. The use of standardized neurobehavioral rating scales has been shown to improve accuracy in distinguishing between coma, unresponsive wakefulness syndrome/vegetative state and minimally consciousness state. The following paper will present an evidence-based approach to neurobehavioral assessment for use in clinical practice. Strategies for optimizing assessment will be provided to improve diagnostic accuracy. Clinical application of an interdisciplinary approach to identifying and managing confounds will be discussed, as well as how assessment results can be used to identify trends in performance and guide prognostic counseling with families.